INGLIZ TILI DARSLARIDA O‘QUVCHILAR TADBIRKORLIK KO‘NIKMALARINI RIVOJLANTIRISHNING PEDAGOGIK SHART-SHAROITLARI - Mirzakarimova, M.M. (SCIENCE and SOCIETY, 2023)
The article describes the pedagogical conditions for the development of entrepreneurial skills of students in the English language classes in the development of the activities of competent individuals and qualified specialists in the process of socio-economic production.